2022
DOI: 10.1186/s12889-022-14690-9
|View full text |Cite
|
Sign up to set email alerts
|

Towards a health promoting university: descriptive findings on health, wellbeing and academic performance amongst university students in Australia

Abstract: Background Universities are increasingly recognised as institutions where health and wellbeing can be promoted to maximise academic outcomes, career transitions, and lifelong positive health behaviours. There is concern about the mental health of university students and other factors which affect academic outcomes particularly for subgroups such as international students. There are few cohort studies of the breadth of issues that can impact on mental health and academic outcomes for both local … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 100 publications
0
17
0
Order By: Relevance
“…The present study examined two waves of data collected through the “Towards a Health Promoting University” study ( Sanci et al, 2022 ), which was based at a single tertiary educational institute in Melbourne, Australia. The baseline survey (Wave 1) was conducted between 2 April to 3 June 2019.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study examined two waves of data collected through the “Towards a Health Promoting University” study ( Sanci et al, 2022 ), which was based at a single tertiary educational institute in Melbourne, Australia. The baseline survey (Wave 1) was conducted between 2 April to 3 June 2019.…”
Section: Methodsmentioning
confidence: 99%
“…The baseline survey (Wave 1) was conducted between 2 April to 3 June 2019. All students who were enrolled at the institution in March/April 2019, and who were over 18 years old were invited to participate in this survey ( Sanci et al, 2022 ). Students enrolled in non-award courses, cross-institutional or exchange programs, and whose status was ‘not admitted’ were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…All undergraduate, postgraduate, and graduate research students aged 18+ and enrolled at the University were invited via direct email to participate in the original 20-min online health and wellbeing survey in 2019. Of the 56,375 students invited, 14,880 students participated in Wave 1 (for full details of methods see Sanci and colleagues [ 25 ]). For Wave 2, all students who responded to the Wave 1 survey and remained enrolled at the university in 2020 were contacted again and invited to participate in a shorter, five-minute Wave 2 online survey.…”
Section: Methodsmentioning
confidence: 99%
“…High levels of student distress have been demonstrated in a number of Australian studies. Sanci [6] found that 1 in 3 of the 14,880 student's surveyed reported experiencing stressors at The University of Melbourne, and comparison of self-report data with academic outcomes showed a clear association between poorer mental health and lower scores. This is less than a national tertiary wellbeing survey conducted by Headspace in 2016.…”
Section: Introduction 11 the Contextmentioning
confidence: 99%
“…Students attending regional universities, located in towns, cities or areas that are geographically beyond Australia's major capital cities such as Melbourne, Sydney, Perth or Brisbane, have been described as experiencing more social isolation, relocation, and financial difficulties than capital city-based students [8]. These dislocation issues seem similar to concerns for international students who have been identified as having access to less social supports whilst simultaneously dealing with stressors of using a second language and experiencing discrimination [6]. A South African study [9] also highlighted how feelings of fear and being disrespected were linked with low levels of wellbeing for marginalised students.…”
Section: Introduction 11 the Contextmentioning
confidence: 99%